Wilf's Conjecture. Issue 6 (1st June 2016) - De Angelis, Valerio; Marcello, Dominic
Abstract: In a Note in this MONTHLY, Klazar raised the question of whether the alternating sum of the Stirling numbers of the second kind is ever zero for n ≠ 2. In this article, we present the history of this problem, and an economical account of a recent proof that there is at most one n ≠ 2 for which B ± ( n ) =0.